Method for grouping of customers and aesthetic design based on rough set theory. Issue 4 (4th July 2018) - Kobayashi, Masakazu; Niwa, Kouki
ABSTRACT: Due to maturation of science and technology, companies are required to differentiate their products in terms of subjective qualities such as aesthetics and ergonomics whose evaluation depends on customer feeling i.e. kansei. To consider customer kansei in product developments, various design methods have been developed, but diversity of customers' kansei is becoming a big issue. More specifically, most of industrial products are designed for many customers, not a single customer, and it is quite difficult to design products that satisfy all customers due to the diversity of their kansei. To overcome this problem, we propose a new method for grouping of customers and aesthetic design based on rough set theory. In the proposed method, customers make kansei evaluation of existing products using SD method. By using rough set theory, rules that describe the relationships between customers' preference and impressions taken from existing products and aesthetic features of existing priducts are extracted from their evaluation results. Customers are then grouped based on the similarities of their extracted rules. New aesthetic designs are finally synthesized by combining extracted rules for each group. Since grouping based on the similarity of rules extracted by rough set theory among customers increases the similarity of the rules which customers in the same group have, there is high possibility that new aesthetic designs synthesized by combining them reflect preferences of all customers in the group. In the case study, the proposed method was applied to a car exterior design to confirm its effectiveness. GRAPHICAL ABSTRACT: